The effects of legislated tax changes in Germany - Bernd Hayo; Matthias Uhl (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
This paper studies the short-run macroeconomic effects of legislated tax changes in Germany using a vector autoregression (VAR) approach. Identification of the tax shock follows the narrative approach recently proposed by Romer and Romer (2010). Results indicate a moderate, but statistically significant, reduction in output as well as a strong offsetting monetary policy reaction following announcement of the tax policy. In response to a 1 percent increase in the tax-to-GDP ratio, the peak output reduction is about 0.7 percent. Distinguishing between anticipation and implementation effects suggests that tax changes affect GDP prior to actual implementation, whereas effects around the implementation period are insignificant, which is arguably due to the offsetting, forward-looking monetary policy reaction.
Keywords: E62; H30; K34; 330; legislated tax change; narrative approach; fiscal policy; tax policy; Steuerpolitik; Schock; Steuerwirkung; Wirtschaftswachstum; Sozialprodukt; Geldpolitik; Deutschland